2019
DOI: 10.1039/c9en00199a
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial homoserine lactones as a nanocomposite fertilizer and defense regulator for chickpeas

Abstract: AHL/Fe-CNF nanocomposites were effective in increasing germination rate and plant growth as well as developing resistance towards biotic and abiotic stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 57 publications
4
33
0
7
Order By: Relevance
“…Moreover, CNFs increase the water uptake ability, germination rate, and nontoxicity even at higher concentration of dose and therefore are used as a growth stimulant of the plants. In a recent study, Gupta et al suggested that the CNFs are used as a carrier to deliver acylated-homoserine lactone in chick pea plants [34]. The study suggested that CNF-acylated homoserine lactone-based composite increased the plant growth as well as stress tolerance ability.…”
Section: Carbon-polymer Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CNFs increase the water uptake ability, germination rate, and nontoxicity even at higher concentration of dose and therefore are used as a growth stimulant of the plants. In a recent study, Gupta et al suggested that the CNFs are used as a carrier to deliver acylated-homoserine lactone in chick pea plants [34]. The study suggested that CNF-acylated homoserine lactone-based composite increased the plant growth as well as stress tolerance ability.…”
Section: Carbon-polymer Compositesmentioning
confidence: 99%
“…and bio-composite nanomaterials have been developed. These NMs are efficiently used in the field of agriculture for production and protection of crops [32][33][34][35]. However, phytotoxicity, degradation of soil, large-scale production, agglomeration, and effective delivery system still remain a concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Рост и развитие растения, ассимиляция питательных веществ, стрессоустойчивость во многом определяются характером такого взаимодействия (22)(23)(24). В QS-регуляции грамотрицательных бактерий задействованы сигнальные соединения класса ацилгомосеринлактонов (АГЛ) (25), которые проявили себя как эффективные стимуляторы роста растений и фитомодуляторы устойчивости к биотическим и абиотическим стрессорам (8,26).…”
unclassified
“…АГЛ влияют на формирование защитной реакции растений, инициируют системную устойчивость и улучшают распознавание патогенных микроорганизмов (97). Праймирование семян Cicer arietinum С4-АГЛ усиливало рост и повышало стрессоустойчивость растений (26). Праймированные семена хорошо прорастали в условиях моделируемого окислительного (5 мМ H2O2) и солевого (200 мМ NaCl) стрессов.…”
unclassified